Pengembangan Buku Ajar Berbasis STEM (Science, Technology, Engineering, Mathematics) Terintegrasi Keislaman pada Mahasiswa Pendidikan Islam Anak Usia Dini - Musrikah Musrikah; Septinaningrum Septinaningrum (JEA (Jurnal Edukasi AUD), 2025)
This study focused on developing a STEM-based textbook integrated with Islamic values for Early Childhood Islamic Education students using the ADDIE development model. Sixty students participated, consisting of 30 in the control group and 30 in the experimental group. Data were obtained through expert validation, student response questionnaires, and learning outcome tests. The validation results showed that the textbook was highly valid, achieving an average score of 91.5%. Statistical analysis indicated that the textbook effectively improved learning outcomes, as the experimental class achieved a higher average score than the control class (82.20 compared to 70.60). The independent sample t-test yielded a Sig. value of 0.00<0.05, confirming a significant improvement in students’ understanding. The gain score of 0.569 placed the textbook’s effectiveness in the moderate category. In addition, student responses were very positive, with an attractiveness rate of 93.7%. The implications of this study confirm that a STEM-based Project based learning (PjBL) textbook integrated with Islamic values can serve as an effective learning resource to enhance student engagement and develop critical thinking skills, thereby supporting the teaching and learning process as well as academic development.